Whistles as Loud as their Recipients? A Framework for Analyzing Complaint Recipients - Rathke, Selina (Student Undergraduate Research E-journal!, 2018)
Tax avoidance, fraud, endangerment of public safety - whistleblowers are crucial for making organizational misconduct transparent. Unsurprisingly, whistleblowing is a commonly researched subject (e.g. Brown, 2008). Yet, only few studies systematically focus on the recipients of whistleblowers’ reports. This lack of attention is striking in light of the decisive role which complaint recipients play in the whistleblowing process (e.g. Lewis, Brown, & Moberly, 2014; Read & Rama, 2003). Drawing on existing literature, this study develops and applies a comparative framework which allows for a comprehensive analysis of whistleblowing recipients. Findings confirm the framework’s utility for answering questions concerning recipients’ involvement and responses. Hence, this study paves the way for the application of a novel analytical focus within whistleblowing research1.